Seasonal and Multiyear Flow Variability on the Prince of Wales Icefield, Ellesmere Island: 2009–2019. Issue 4 (5th April 2022) - Dalton, Abigail; Van Wychen, Wesley; Copland, Luke; Gray, Laurence; Burgess, David
Abstract: Over the last two decades, Trinity, Wykeham, Ekblaw, and Cadogan glaciers have retreated and been identified as the primary sources of iceberg flux from Prince of Wales (POW) Icefield, Ellesmere Island, accounting for ∼83% of total solid ice discharge. In this study, we used a total of 167 Radarsat‐2 Synthetic Aperture Radar scene pairs collected between 2009 and 2019 to derive winter surface velocities of these four major basins of the POW Icefield. Over this period both Cadogan and Ekblaw glaciers underwent multiyear acceleration and deceleration limited to their lower parts, consistent with characteristics of "pulse‐type" glaciers. Trinity and Wykeham glaciers are currently the fastest flowing glaciers in the CAA and are grounded below sea level for ∼40 km up‐glacier from their termini. Both glaciers underwent multiyear repeating periods of velocity acceleration between 2009 and 2019 which coincided with significant thinning at their termini. As of 2017, Trinity and Wykeham were each within ∼10 m of flotation over their lowermost 4 km. We also identified a shift in flow since 2014 on Trinity and Wykeham, after which winter flow rates began to propagate up‐glacier and were nearly identical to flow rates observed throughout the rest of the year, indicating that seasonal variability in flow has become less apparent in recent years. Our findings suggest that Trinity and Wykeham glaciers have transitioned to a flow type dominated by dynamic thinning, which is strongly influenced by subglacial topography and may be susceptible to instability of the glacier front and large‐scale collapse. Plain Language Summary: Trinity, Wykeham, Ekblaw, and Cadogan are the four primary glacier basins on the Prince of Wales (POW) Icefield, and are responsible for the majority of solid ice discharged from it. Previous work on tidewater glacier dynamics in the Canadian Arctic has mainly focused on quantifying surface velocities and ice fluxes to the ocean, but less research has been undertaken on the physical processes controlling variability in glacier flow. Here, we use remote sensing methods to measure changes in ice flow, surface elevation, and terminus buoyancy to identify the processes controlling glacier motion in this region. We find that ice flow of the four major glaciers on the POW Icefield are strongly controlled by their underlying bed topography. Trinity and Wykeham glaciers are two of the fastest flowing glaciers in the Canadian Arctic and appear to have recently entered a period of instability at their termini, which, if they continue at the current rates of thinning, could lead to their large‐scale acceleration, retreat, and collapse. Key Points: We report updated winter velocity and surface elevation change estimates for four major basins on the Prince of Wales Icefield Flow for Trinity, Wykeham, Cadogan, and Ekblaw glaciers is strongly influenced by bed topography Velocity changes, surface thinning, and terminus buoyancy resulted in instability and near flotation of the termini of Trinity and Wykeham glaciers